Espécies vegetais com potencial atividade anti-infamatória: caracterização fitoquímica e atividades anti-TNF-α e antiartrítica de Stryphnodendron adstringens (MART.) Coville. - Bárbara Oliveira Henriques (2016)
TNF-α is considered one of the main cytokine involved in the inflammatory process. This cytokine and radical oxygen species play an important role in the etiology of various inflammatory diseases such as ulcerative colitis and rheumatoid arthritis. Ulcerative colitis is a chronic, relapsing, idiopathic and inflammatory disease of gastrointestinal tract. Rheumatoid arthritis is a chronic inflammatory disease of the synovial space which results in damage to the articular cavity, bone erosion and changes in joint integrity. Both diseases have not had therapy therapeutic options effective. Thus, this study aimed to evaluate the antioxidant and TNF-α production inhibition activities of plant extracts, fractions and isolated substances, to identify bioactive constituents for the treatment of inflammatory diseases, especially ulcerative colitis and rheumatoid arthritis. A total of 13 plant species was selected for screening based on ethnopharmacological and chemossistematic criteria. Ethanol extracts of the species were initially assayed in vitro, for inhibiting TNF-α production by THP-1 cells stimulated by lipopolysaccharide (LPS). Antioxidant activity of the ethanol extracts was assayed, in vitro, in DPPH model. Based on results of the initial screening, ethanol extracts of Campomanesia lineatifolia, Stryphnodendron adstringens and Terminalia glabrescens were considered active, and were then subjected to fractionation by liquid-liquid partition between immiscible solvents and evaluated for their anti-inflammatory activity in vivo model of inflammation induced by LPS in the joint cavity. The aqueous and organic fractions of S. adstringens (SAA and SAO), administered orally at doses 10, 100 and 1000 mg/kg, induced a significant anti-inflammatory response, with a reduction dose-dependent in the migration of leukocytes to the inflammatory site. The fraction enriched in polyphenols, SAO2, and 4'-O-methyl-gallocatechin, SAO1, also exhibited this activity, respectively, at the doses 10, 50 and 100 mg/kg and 5, 10 and 20 mg/kg. The fractions SAO and SAO2 were also effective in inhibiting, in the same doses, leukocyte migration in a dose-dependent manner, in a model of antigen-induced arthritis (AIA); SAO1 showed this ability only in the higher dose evaluated, 20 mg/kg. SAO2 fraction failed to alleviate the effects of ulcerative colitis in mice stimulated by TNBS, at dose 50 mg/kg. The organic fraction S. adstringens was subjected to chromatographic fractionation by useful techniques. In the obtained fractions, it was identified the presence of gallic acid, gallocatechin, epigallocatechin and epigallocatechin gallate, and isolated the 4'-O-methyl-gallocatechin, identified by standard spectroscopic techniques. The analysis of SAO by UPLC-MS yield the identification of gallic acid and 11 prodelphinidins, that 4 were described for the first time in the species.